Well-to-Wheel Greenhouse Gas Emissions from Flying Cars: A Focus on Air Shuttles - Xiong, Yansen (International Journal of Electric Power and Energy Studies, 2024)
Flying cars are becoming a key technology in future transportation, because of their ability to travel fast and to reduce traffic jams. Air shuttles are an important application scenario of flying cars. They can carry 19 passengers, playing a similar role as medium on-road buses. However, it is still unclear which has a better performance on carbon emissions, air shuttles or road buses. Based on the analysis of the flying car’s flying process, lifecycle greenhouse gas emissions from flying cars which are used as air shuttles are calculated and further compared with on-road bus emissions. For thorough consideration, improvements in battery specific energy are considered, and different propulsion systems for buses are also calculated. The results show that at the current battery technology level (200 Wh/kg specific energy), air shuttles have much more emissions than all kinds of road buses. But if the battery technology progresses to the level of 2030 (400 Wh/kg specific energy as predicted), air shuttles will have a lower emission than fuel cell buses within the range of 250 km, and will be competitive with battery electric bus that carries an equal number of passengers.